Proceedings of the 2019 European Conference on Computing in Construction 2019
DOI: 10.35490/ec3.2019.192
|View full text |Cite
|
Sign up to set email alerts
|

Semantic data mining and linked data for a recommender system in the AEC industry

Abstract: Even though it can provide design teams with valuable performance insights and enhance decision-making, monitored building data is rarely reused in an effective feedback loop from operation to design. Data mining allows users to obtain such insights from the large datasets generated throughout the building life cycle. Furthermore, semantic web technologies allow to formally represent the built environment and retrieve knowledge in response to domain-specific requirements. Both approaches have independently est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This study suggested that future research directions include the identification of data types, assessment of ontology performance and creation of opensource approaches. A second recent study [5] proposed a conceptual system architecture for semantic data mining and linked data for a system that generates recommendations for performance-oriented design in architecture, engineering and construction. Themes that emerge from the literature include the following: (i) semantic queries can enable access to knowledge graphs; (ii) traditional data mining techniques can allow sensor data mining; (iii) the use of a linked building data graph empowers semantic data mining; and (iv) the use of pattern matching in combination with Resource Description Framework (RDF) stream processing can occur with RDF graph mining [5].…”
Section: Introductionmentioning
confidence: 99%
“…This study suggested that future research directions include the identification of data types, assessment of ontology performance and creation of opensource approaches. A second recent study [5] proposed a conceptual system architecture for semantic data mining and linked data for a system that generates recommendations for performance-oriented design in architecture, engineering and construction. Themes that emerge from the literature include the following: (i) semantic queries can enable access to knowledge graphs; (ii) traditional data mining techniques can allow sensor data mining; (iii) the use of a linked building data graph empowers semantic data mining; and (iv) the use of pattern matching in combination with Resource Description Framework (RDF) stream processing can occur with RDF graph mining [5].…”
Section: Introductionmentioning
confidence: 99%